Ready player one? a conceptual analysis on the dynamics of critical thinking and meta cognition in game-based language learning - Supian, Nadya; Mohd Asraf, Ratnawati; Idris, Wan Irma Sabrina; Hamzah, Hasleena (Blue Eyes Intelligence Engineering and Sciences Publication, 2019)
21st century learning involves mastering the 4 C’s, namely Critical Thinking, Communication, Collaboration, and Creativity. One pedagogical application that potentially capitalis-es these elements is game-based language learning in Multi-User Virtual Environments (MUVEs), such as massively multiplayer online role-playing games MMORPGs for learning English for Specific Purposes (ESP). This paper presents a conceptual analy-sis of how critical thinking and meta cognition are represented and interact with each other in game-based learning frameworks. We begin with an overview of game-based learning, a review of critical thinking in game-based language learning, followed by an analysis of the role of meta cognition in game-based language learning. Finally, a discussion on 4 game-based learning frame-works will be presented. By studying the interplay between criti-cal thinking, meta cognition and game-based language learning, we argue for the need to develop a holistic framework that ex-plains how these relate with each other, in order to further devel-op the pedagogical potential of using game-based language learning.